KNOWLEDGE OF MEDICAL PROFESSIONALISM AMONG THE UNDERGRADUATE STUDENTS OF ARMY MEDICAL COLLEGE, RAWALPINDI - Aleem, Shoaib Bin; Raja, Amna Kaneez Fatima; Iqbal, Mishal; Naveed, Tahoora; Yousaf, Iktekhar; Gul, Farah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the knowledge about medical professionalism of pre clinical and clinical MBBS and BDS students. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at Army Medical College. The duration from its approval by the Ethics Review Board to the writing of the manuscript was of 6 months, from May 2019 to Sep 2019. Methodology: Second and final year MBBS and BDS students were asked to complete a questionnaire. It was designed to assess the participants’ knowledge of professionalism. Mean scores were compared in each course between the two years and between the same years but different courses. SPSS-23 was used for statistical analysis. Results: The number of participants of this study was 454. The total mean score was 12.94 ± 2.01 the mean scores of females and males were not significantly different. The final year MBBS mean score was 13.18 ± 1.49 while the second year MBBS mean score was 12.85 ± 1.99 they were not significantly different. While the final year BDS the mean score of 13.95 ± 1.91 was significantly higher than the second year BDS score of 11.18 ± 2.96. Second year MBBS had a significantly higher score than second year BDS, the result was opposite in final year with regards to the course. Conclusion: The statistically insignificant difference between the scores of second year and final year MBBS was because of medical professionalism not being formally taught.